Assessing the causal impact of the 3-point per victory scoring system in the competitive balance of LaLiga - Soto-Valero, C.; Pic, M. (International Journal of Computer Science in Sport, 2019)
Competitive balance is a key concept in sport because it creates an uncertainty on the outcome that leads to increased interest and demand for these events. The Spanish Professional Football League (LaLiga) has been one of the top European leagues in the last decade, and it has given rise to a particular research interest regarding its characteristics and structure. Since season 1995/96, LaLiga changed the number of points given to the winning teams, by awarding three points per victory instead of two. In this paper, we assess the impact of such a change on the competitive balance of LaLiga. Our analysis focuses on teams with varying levels of performance and follows a three-step approach. First, we cluster the teams according to their historical performance using an adjusted measure based on their credible intervals of winning ratios. Second, we calculate Kendall`s tau coefficient (according to our adjusted measure) in order to obtain the overall ranking turnover of teams between consecutive seasons. Third, we assess the causal impact of the adoption of the new scoring system, based on Kendall`s tau coefficients, for each cluster of teams. Our results show that the overall competitive balance decreased after the adoption of the new scoring system. However, the impact was not the same for all teams, being more significant for top teams and less significant for bottom teams. Moreover, our predictions using adjusted ARIMA models indicate that this difference in the competitive balance will persist for future seasons.